Assessing the potential for resource competition between the Kerguelen Plateau fisheries and southern elephant seals - Hindell, Mark Andrew; McMahon, Clive Reginald; Guinet, Christophe; Harcourt, Rob; Jonsen, Ian David; Raymond, Ben; Maschette, Dale (Frontiers in Marine Science, 2022)
Indirect ecological interactions such as competition for resources between fisheries and marine predators have often been proposed but can be difficult to demonstrate empirically. The Kerguelen Plateau in the Southern Indian Ocean supports fisheries for both Patagonian toothfish and mackerel icefish and is also an important foraging ground for several avian and mammalian predators, including the southern elephant seal. We quantified the spatio-temporal use of the plateau by southern elephant seals and found that males and females spent 30% of their time on the plateau within the commonly used fishing grounds, indicating the possibility of competition for resources there. We then contrasted the seals’ use of two habitat types, the benthos (where interactions with the long-line fisheries are most likely) and the epi-pelagic zone. The likelihood of feeding on the benthos declined as ocean depth increased and was also less likely at night. Males were also more likely to feed on the benthos than females. The sub-adult male seals consumed an estimated 6,814 – 14,848 tons of high energy content prey (including toothfish) and females 7,085 – 18,037 tons from the plateau during the post-molt winter months. For males this represented 79.6 - 173.4% of the mean annual catch by the Kerguelen fishery compared to 82.8 - 210.7% for adult females. When considering the seals consumption of fish from the benthos within the fishing grounds these estimates decreased to 3.6 - 15.1% of the fishery’s total annual catch for females and 7.8 - 19.1% for males. While this further indicates the possibility of indirect ecological interactions (with the fishery taking more fish than the seals), the lack of detailed diet information for the seals precludes us from establishing the degree or nature of the possible interactions because the importance of toothfish and icefish in the diet of the seals is unknown. However, the unique life history and highly polygynous nature of this species, and the lack of evidence of a measurable effect on either the seal’s population growth rates or the catch per unit of the fishery, suggest that any indirect ecological interactions are not of sufficient magnitude to affect either the seal population or the fishery.